PENDAMPINGAN DALAM MEMAHAMI INVESTASI HUMAN CAPITAL DORONG PEMBANGUNAN BERKUALITAS MELALUI PENDIDIKAN - Umalihayati Umalihayati; Popi Dayurni; Muhammad Hidayat (STAI Darul Qalam Tangerang, 2023)
Educational investment can be undertaken not only achieved by perfunctory efforts. Education must be in line with good quality, excellent, innovative, and competitive. To achieved a good quality education, students must be reinforced with knowledge in facing competitive global challenges. Universities as providers of higher education system can be firm and clear in charting the direction of education to have an impact on increasing the development in Indonesia, especially the lecturers as the spearhead in the implementation of education. The purpose of mentoring is to gain an increasing in students' understanding in analysing human capital investment to encourage quality development